Stem cell sprays for neurological injuries: a perspective. Issue 4 (29th October 2021) - Woods, William; Evans, Daisy; Mogas Barcons, Aina; Tzerakis, Nikolaos; Adams, Christopher; Maitreyi Chari, Divya
Abstract : Injuries to the brain and spinal cord have major clinical consequences with high costs for healthcare systems. Neural cell transplantation therapies have significant translational potential to promote regeneration post-injury with clinical trials commencing for various pathologies. However, there are challenges associated with current clinical approaches used for systemic or direct delivery of transplant cells to neural tissue in regenerative applications. These include risks associated with surgical microinjection into neural tissue (e.g. haemorrhage, cell clumping) and high cell loss due to systemic clearance or with cell passage through fine gauge needles into densely packed neural tissue. This article presents lines of evidence supporting the concept that cell spray delivery technology can offer significant translational benefits for neural transplantation therapy, versus current cell delivery methods. Potential benefits include rapid/homogenous cell delivery, release over large surface areas, minimal invasiveness, compatibility with neurosurgical procedures in acute injury, no predictable clinical complications and the capacity to combine cell therapies with drug/biomolecule delivery. Accordingly, we consider that the development of cell spray delivery technology represents a key goal to develop advanced cell therapies for regenerative neurology.